The ROS‐responsive scavenger with intrinsic antioxidant capability and enhanced immunomodulatory effects for cartilage protection and osteoarthritis remission. (March 2022) - Xiong, Hao; Wang, Shuqin; Sun, Zhenghua; Li, Juehong; Zhang, Haolan; Liu, Weixuan; Ruan, Jihao; Chen, Shuai; Gao, Changyou; Fan, Cunyi
Highlights: To achieve both reactive oxygen species (ROS) responsive scavenging ability and drug targeted delivery ability, a novel polymer (PEG-PTK-PEG) was synthesized through a simple and direct reaction between polythioketal (PTK) and m-PEG-acrylate. The degradation products of PEG-PTK-PEG responding to the ROS accumulating microenvironment also have excellent biocompatibility and extremely low toxicity. In the OA model, the PEG-PTK-PEG@ASTA could effectively inhibit the expression of ROS, thereby downregulating the MAPK signaling pathway and inducing the conversion of macrophages from the M1 phenotype to the M2 phenotype. The synergistic effect of PEG-PTK-PEG's ROS-responsive drug delivery ability and ROS scavenging ability provide a new and effective strategy for the clinical treatment of OA and other inflammatory diseases. The synergistic functions of the PEG-PTK-PEG@ASTA NPs were attributed to the fact that the main chain of the PEG-PTK-PEG can be cleaved under the induction of ROS, and this process can consume a large amount of ROS. Abstract: Oxidative stress has close relationship with the progression of osteoarthritis and thus is an important therapeutic target. The use of antioxidants alone has common disadvantages such as low bioavailability, poor stability, and rapid joint clearance or toxicity at high concentrations. To achieve both reactive oxygen species (ROS) responsive scavenging ability and drug targeted delivery ability, a novel polymer (PEG-PTK-PEG) was synthesized through a simple and direct reaction between polythioketal (PTK) and m-PEG-acrylate. In addition to excellent mechanical properties and high drug loading capacity, the degradation products of PEG-PTK-PEG responding to the ROS accumulating microenvironment also have excellent biocompatibility and extremely low toxicity. Further, the PEG-PTK-PEG nanoparticles (NPs) loaded with astaxanthin (ASTA), which is an antioxidant with high biological safety, could effectively reduce ROS expression and release ASTA slowly and accurately in the area of high ROS expression as a result of the polymer degradation. In the OA model, the PEG-PTK-PEG@ASTA could effectively inhibit the expression of ROS, thereby downregulating the MAPK signaling pathway and inducing the conversion of macrophages from the M1 phenotype to the M2 phenotype. The synergistic effect of PEG-PTK-PEG's ROS-responsive drug delivery ability and ROS scavenging ability significantly promoted the therapeutic effect of OA, providing a new and effective strategy for the clinical treatment of OA. Graphical abstract: The PEG-PTK-PEG nanoparticles (NPs) loaded with astaxanthin (ASTA) can effectively reduce ROS and release ASTA slowly and accurately in the area of high ROS expression as the polymer degradation. In the OA model, the PEG-PTK-PEG@ASTA can effectively inhibit the expression of ROS, thereby downregulating the MAPK signaling pathway and inducing the conversion of macrophages from the M1 phenotype to the M2 phenotype. Image, graphical abstract